A new dispersible moist wipe from wetlaid/spunlace nonwoven: Development and characterization. (February 2019) - Zhang, Yinjiang; Deng, Chao; Wang, Yuxiao; Huang, Chen; Zhao, Yi; Jin, Xiangyu
Wood pulp/Danufil nonwovens have been prepared by wetlaid/spunlace method as a potential and new dispersible moist wipes. To verify the potential applications of the wetlaid/spunlace nonwovens, this study investigated the wet strength, softness/smoothness, and dispersibility of wetlaid/spunlace nonwovens with different Danufil contents and length-to-diameter ratios. Meanwhile, these properties were compared with three other types of commonly-used dispersible moist wipes. The results show that an increase in Danufil content or length-to-diameter ratio results in increasing wet strength and decreasing dispersibility of wetlaid/spunlace nonwovens. However, an increase in pulp content or Danufil length-to-diameter ratio will increase real softness and weaken felt smoothness of materials. In addition, the average machine and cross directions wet strength are 9.5 N/50 mm and 6.3 N/50 mm, respectively. The real softness and corresponding felt smoothness of wetlaid/spunlace nonwovens range from 10.8 to 16.3 and from 37.1 to 22.0, respectively. The average required dispersion time of wetlaid/spunlace nonwovens are controlled within 21 min. Overall, the wood pulp/Danufil wetlaid/spunlace nonwovens have the similar wet strength but excellent softness/smoothness and dispersibility when compared with the currently used dispersible products, and possess high feasibility and potential for dispersible moist wipes industry.